What to expect when you're expecting [videorecording (DVD)] - Jones, Kirk, 1964-; Lopez, Jennifer, 1970-; Diaz, Cameron; Quaid, Dennis (Lionsgate, 2012)
A look at love through the eyes of five interconnected couples experiencing the thrills and surprises of having a baby, and ultimately coming to understand the universal truth that no matter what you plan for, life doesn't always deliver what's expected.